Religious Liberties for Corporations? - Gans, D. author. aut Link
VI, 80 p.
Keywords: An expanded version of a series of debates between the authors, this book examines the nature of corporate rights, especially with respect to religious liberty, in the context of the controversial Hobby Lobby case from the Supreme Court's 2013-14 term.